Family-Based Nutritional Assistance to Improve Knowledge, Attitudes, and Nutritional Status of Pregnant Women with Chronic Energy Deficiency in Karangtengah Village - Hesti Kurniasih; Fitria Zuhriyatun; Riza Amalia (CV Media Inti Teknologi, 2026)
Background: Chronic Energy Deficiency (CED) among pregnant women remains a major public health concern in Indonesia, as it increases the risk of adverse maternal and neonatal outcomes. Family support plays an important role in improving maternal nutritional practices. Aims: This study aimed to evaluate the effectiveness of a family-based nutritional assistance model in improving the nutritional status of pregnant women with Chronic Energy Deficiency and reducing the risk of low birth weight. Methods: A quasi-experimental study with a pretest–posttest design was conducted among pregnant women with CED in Karangtengah Village. The intervention included nutrition education, family empowerment, home visits, nutritional monitoring, counseling, and the provision of a supplementary meal guidebook based on locally available foods. Outcomes were assessed through changes in knowledge, attitudes, Mid-Upper Arm Circumference (MUAC), and body weight before and after one month of intervention. Result:s The proportion of participants with good nutritional knowledge increased from 20% to 80%, while positive attitudes toward maternal nutrition increased from 40% to 90%. Mean MUAC improved from 22.40 ± 0.83 cm to 23.05 ± 0.79 cm, and mean body weight increased from 48.20 ± 3.52 kg to 49.35 ± 3.47 kg after one month of assistance. All participants received and utilized the supplementary meal guidebook to support healthy dietary practices during pregnancy. Conclusion: The family-based nutritional assistance program improved knowledge, attitudes, and nutritional status among pregnant women with CED. The involvement of family members, midwives, and nutrition cadres, combined with practical dietary guidance, supports the feasibility of this community-based approach to improving maternal nutrition during pregnancy.